Transforming Early Learning in Indonesia: Interactive Technology Integration in English Language Education for Young Learners - Nasution, Dina Syarifah (Universitas Pahlawan Tuanku Tambusai, 2024)
This research delves into the dynamic and evolving landscape of early learning in Indonesia, focusing on the transformative impact of integrating interactive technology into the educational milieu. The primary exploration centers on English language education for young learners, delving into the multifaceted challenges, opportunities, and implications entwined with integrating interactive technology in this specific educational context. Within this study, the research meticulously navigates the intricate complexities associated with implementing technology, scrutinizing its effectiveness in captivating the attention of young and impressionable minds. Furthermore, it seeks to discern the far-reaching consequences of this integration on language acquisition, acknowledging technology's pivotal role in shaping linguistic development during the formative years. Through a nuanced and meticulous examination of current practices and the illumination offered by insightful case studies, this paper aspires to serve as a guiding beacon. It aims to provide valuable insights that not only shed light on the challenges and opportunities inherent in merging interactive technology with early English language education but also pave the way for a more enhanced and practical instructional approach for young learners in Indonesia. This research contributes to the ongoing discourse on innovative pedagogical methodologies, positioning technology as a catalyst for positive transformation in early learning environments.